2022
DOI: 10.1021/jacs.1c13396
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the N≡N Triple Bond from Reductive Coupling of a Paramagnetic Diruthenium Nitrido Compound

Abstract: Construction of nitrogen−nitrogen triple bonds via homocoupling of metal nitrides is an important fundamental reaction relevant to a potential Nitrogen Economy.Here, we report that room temperature photolysis of Ru 2 (chp) 4 N 3 (chp − = 2-chloro-6hydroxypyridinate) in CH 2 Cl 2 produces N 2 via reductive coupling of Ru 2 (chp) 4 N nitrido species. Computational analysis reveals that the nitride coupling transition state (TS) features an out-of-plane "zigzag" geometry instead of the anticipated planar zigzag T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
2
13
0
Order By: Relevance
“…A smaller increase in nitride character in the π* orbitals is observed for [Cr V NSal NMe2 ] •+ in agreement with ligand-based oxidation, and a substantially slower rate of decay. Interestingly, a larger increase in the nitride character in the π* orbitals is calculated for Mn VI in comparison to Cr VI (Table S3), which matches the observation of facile homocoupling for the oxidized Mn VI complexes. ,, It is possible that excited states with nitride radical character are energetically accessible for the oxidized Mn VI complexes or that radical character develops along the homocoupling reaction coordinate, accelerating the homocoupling process. , While outside the scope of the current work, further insight could be gained by reaction profile and complete-active space self-consistent-field calculations (CASSCF). ,, …”
Section: Results and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A smaller increase in nitride character in the π* orbitals is observed for [Cr V NSal NMe2 ] •+ in agreement with ligand-based oxidation, and a substantially slower rate of decay. Interestingly, a larger increase in the nitride character in the π* orbitals is calculated for Mn VI in comparison to Cr VI (Table S3), which matches the observation of facile homocoupling for the oxidized Mn VI complexes. ,, It is possible that excited states with nitride radical character are energetically accessible for the oxidized Mn VI complexes or that radical character develops along the homocoupling reaction coordinate, accelerating the homocoupling process. , While outside the scope of the current work, further insight could be gained by reaction profile and complete-active space self-consistent-field calculations (CASSCF). ,, …”
Section: Results and Discussionsupporting
confidence: 71%
“…63,84 While outside the scope of the current work, further insight could be gained by reaction profile and complete-active space self-consistentfield calculations (CASSCF). 6,34,84 The relatively slow homocoupling rate for the oxidized Cr complexes herein provided an opportunity to probe nitride reactivity differences based on metal ([Cr VI NSal R ] + ; R = CF 3 , tBu) or ligand-based oxidation ([Cr V NSal NMe2 ] •+ ). Previous studies by Brown and Mayer have detailed the increased electrophilicity of charged metal oxo complexes in comparison to their neutral complexes, 85−87 and Holland et al have recently reported a switch from nucleophilic to electrophilic nitride reactivity upon both metal and ligand oxidation (amide to nitroxide) of a Re V nitride complex with a PNP pincer ligand.…”
Section: ■ Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…[2] Therefore, N 2 activation under mild conditions has become a hot research topic. Metal complexes including Mo, [3][4][5][6] Zr, [7] Fe, [8][9][10][11] Ti, [12] W, [13][14] Ru [15] and so on are commonly used for N 2 activation. The activation mechanism involves filled d orbitals for donating electron into π* orbitals of N 2 as well as empty metal d orbitals for accepting electrons from N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxo (M=O) and nitrido (M≡N) species are important classes of high-valent transition metal complexes . On one hand, metal oxo species have long been used as oxidants in chemical and biological systems. On the other hand, the oxidation chemistry of M≡N is much less explored, although metal nitrido species are potentially useful nitrogenation reagents. Attempts to design highly oxidizing/electrophilic metal nitrido species, such as the use of weakly coordinating ancilliary ligands or to increase the oxidation state of the metal centers, are hampered by the relative ease of the nitrido ligands to undergo bimolecular coupling to give dinitrogen. …”
mentioning
confidence: 99%